2022
DOI: 10.3390/jcm11051234
|View full text |Cite
|
Sign up to set email alerts
|

Post-SARS-CoV-2 Acute Telogen Effluvium: An Expected Complication

Abstract: Post-SARS-CoV-2 telogen effluvium has been described in case reports of COVID-19 patients. We evaluated the prevalence of post-SARS-CoV-2 telogen effluvium in patients from a single medical center, exploring any causal links with the infection. Our hospital-based, cross-sectional study was conducted with patient participants discharged with a diagnosis of SARS-CoV-2 pneumonia from 1 March to 4 April 2020. All patients were evaluated by the same senior dermatologist; a clinical/dermatoscopic evaluation was perf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
14
1
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(21 citation statements)
references
References 31 publications
4
14
1
2
Order By: Relevance
“…Monari et al [ 26 ], in a cross-sectional study which enrolled 96 patients with a diagnosis of SARS-CoV-2 pneumonia, identified TE in 31.3% of patients, with a significant difference in sex (females 73%, males 26.7%). The average time detected from the onset of the first symptoms to TE was 68.43 days.…”
Section: Sars-cov-2 Related Covid-19 and Hair Lossmentioning
confidence: 99%
“…Monari et al [ 26 ], in a cross-sectional study which enrolled 96 patients with a diagnosis of SARS-CoV-2 pneumonia, identified TE in 31.3% of patients, with a significant difference in sex (females 73%, males 26.7%). The average time detected from the onset of the first symptoms to TE was 68.43 days.…”
Section: Sars-cov-2 Related Covid-19 and Hair Lossmentioning
confidence: 99%
“…We included eight studies in the dermatological section (Table 5). The most common affection reported was telogen effluvium, often reported between 1 to 3 months post infection [45][46][47][48][49][50][51]. Other clinical findings are low hair density and softer hair, which marks positive to the traction test, and empty follicles using trichoscopy and Trichogramma [45][46][47][48][49][50][51].…”
Section: Mazza M Et Al 2020mentioning
confidence: 99%
“…The most common affection reported was telogen effluvium, often reported between 1 to 3 months post infection [45][46][47][48][49][50][51]. Other clinical findings are low hair density and softer hair, which marks positive to the traction test, and empty follicles using trichoscopy and Trichogramma [45][46][47][48][49][50][51]. The least common hair-loss pattern was the bitemporal-frontal in 5.12% of cases, followed by front vertical in 7.69% and occipital in 12.82%; the most common pattern was the bitemporal and diffuse affection in 30.76% and 43.58%, respectively [46].…”
Section: Mazza M Et Al 2020mentioning
confidence: 99%
See 2 more Smart Citations